Avaliação da perda de massa de revestimento duro depositado por soldagem com arame tubular de liga FeCrC-Ti - Colaço, Fernando Henrique Gruber (2013)
In this work we have studied the mass loss of hardfacing applied by flux cored arc welding. Heat input, shielding gas and number of layers coating. Were changed to application of Fe-Cr-Ti-C self-shielded tubular wire. Single beads were deposited on plates of carbon steel AISI 1020 to analyze the morphology, hardness and dilution. For the analysis of mass loss were deposited beads forming overlapped layers coatings. By means of image analysis measurements were made of the reinforcement, width and penetration and, consequently, the dilution obtained. Hardness measurements were performed on cross-section of the beads and the surface of the specimens of wear. Rubber wheel abrasion tester was used to access the mass loss of coatings. The coatings had retained austenite and martensite microstructure with carbides finely dispersed in the matrix. The main factors that contributed to the increase in mass loss were the cracks due to higher cooling rate of the samples deposited with low heat input, the dilution in the first layer of all samples also contributed to the increase in mass loss. The smallest mass losses were those deposited coatings with high heat input the second and fourth layer, the samples AC2, AC4 and AS2. The volume fraction of titanium carbides contributed to the decrease in the mean free path between the particles of carbides increase the wear resistance of the coatings.